Electric generator based on triboelectric effect - Chan, Tak Fook (Nanyang Technological University, 2023)
Triboelectrification was discovered long time ago. It is only recently that the electric generators based on triboelectrification have attracted a lot attention. When two materials with different electron affinities are brought into physical contact, the difference in the electron affinities would induce electrons to transfer from the lower affinity material to the high affinity material. When they are separated, the transferred electrons induce a current flowing in the external closed circuit. Thus, electrical energy is generated by converting mechanical energy. In this project, the student is required to construct a pair of materials with different electron affinities. The electron transfer efficiency will be studied in terms of the surface properties of the materials. A successful demonstration of the energy converter and a deep understanding of the physical working principle define satisfactory completion of the project.